Corn Hybrid, Row Spacing, and Seeding Rate Effects on Yield in Upstate Missouri. Issue 1 (16th October 2015) - Nelson, Kelly A.; Dudenhoeffer, Christopher J.; Nelson, Scott; Harder, Dana
Abstract : Corn ( Zea mays L.) growers continue to show interest in identifying hybrids that offer high yields in narrow rows (<30 inches). Research evaluated the response of 10 phenotypically different hybrids planted at 30, 000 and 36, 000 seeds/acre in 15‐ and 30‐inch rows from 2011 to 2013 under dry growing conditions in Missouri. Precipitation was up to 35% less (2012) than the 10‐year average in the region during this research. Grain yields were 2.7% greater in 15‐inch rows than in 30‐inch rows when averaged over seeding rate and hybrid, with four of the 10 hybrids having greater yields in narrower rows. Drought affected overall yields, though an early‐maturing hybrid (P0461HR) and a drought‐tolerant hybrid (P1151AM) yielded more than the others. The higher‐yielding hybrids showed no yield difference based on row spacing. In 15‐inch rows, high ear placement and short plants of an early‐maturing hybrid (P0461HR) with average drought tolerance and a late‐maturing hybrid (33T57) with above‐average drought tolerance yielded more than a hybrid (P0621HR) with average drought tolerance and low ear placement, but yields were similar in 30‐inch rows. However, with both row spacings, late‐maturing, drought‐tolerant hybrids yielded more than hybrids with below‐average drought tolerance. Corn seeded at 30, 000 seeds/acre (27, 900 plants/acre at harvest) yielded 25% more in an extreme drought year (2012) than corn seeded at 36, 000 seeds/acre (32, 600 plants/acre at harvest), but no yield difference appeared in 2011 and 2013. Our study indicates that appropriate plant densities and hybrid selection were needed to successfully integrate narrow‐row corn into drought‐prone claypan soils.